2013
DOI: 10.1038/mi.2012.131
|View full text |Cite
|
Sign up to set email alerts
|

Acute helminth infection enhances early macrophage mediated control of mycobacterial infection

Abstract: Co-infection with mycobacteria and helminths is widespread in developing countries, but how this alters host immunological control of each pathogen is not comprehensively understood. In this study, we demonstrate that acute Nippostrongylus brasiliensis (Nb) murine infection reduce early pulmonary mycobacterial colonization. This Nb-associated reduction in pulmonary Mycobacterium tuberculosis colony-forming units was associated with early and increased activation of pulmonary CD4 T cells and increased T helper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…The mechanistic basis for the enhanced-susceptibility to M. tuberculosis of those coinfected mice was mainly IL-4 receptor–mediated alternative activation of macrophages. In contrast, another study has reported that acute infection with N. brasiliensis actually boosts early macrophage-mediated control of infection with BCG 34 . However, it must be noted that BCG does not express certain genes 35 encoding molecules that control the virulence and intracellular survival of mycobacteria 36 ; therefore, it is not clear that such a boosting effect would occur during infection with M. tuberculosis .…”
Section: Tuberculosis and Concurrent Helminth Infectionmentioning
confidence: 85%
“…The mechanistic basis for the enhanced-susceptibility to M. tuberculosis of those coinfected mice was mainly IL-4 receptor–mediated alternative activation of macrophages. In contrast, another study has reported that acute infection with N. brasiliensis actually boosts early macrophage-mediated control of infection with BCG 34 . However, it must be noted that BCG does not express certain genes 35 encoding molecules that control the virulence and intracellular survival of mycobacteria 36 ; therefore, it is not clear that such a boosting effect would occur during infection with M. tuberculosis .…”
Section: Tuberculosis and Concurrent Helminth Infectionmentioning
confidence: 85%
“…Previous studies suggest that early innate recognition of bacteria has the potential to overcome the normally detrimental impact of helminth infection on resistance to bacterial infection [44,45]. Furthermore helminth expanded resident MΦ have been shown to exert a protective effect in models of sepsis [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-4 and IL-10 deficiency was necessary to reverse the obstructing effect of H. polygyrus infection on the CD8 + T cell response toward Toxoplasma (Marple et al, 2017). The majority of co-infection studies despite being protozoan, viral or bacterial infection, have focused on infections with helminth first due to their ability to downmodulate immune responses (Rousseau et al, 1997; Liesenfeld et al, 2004; Chen et al, 2005, 2006; Graham et al, 2005; Su et al, 2005, 2014a,b; Weng et al, 2007; Khan et al, 2008; Noland et al, 2008; Miller et al, 2009; Frantz et al, 2010; Dias et al, 2011; Potian et al, 2011; Kolbaum et al, 2012; du Plessis et al, 2013; Osborne et al, 2014; Budischak et al, 2015; Coomes et al, 2015; Gondorf et al, 2015; Rafi et al, 2015; Obieglo et al, 2016). In light of the fact, that Th2 immunity against helminths is an ongoing challenge in humans and livestock, we aimed to investigate how a previous protozoan infection affects the development of Th2 responses in CD4 + T cells and protection against helminths.…”
Section: Introductionmentioning
confidence: 99%